Cook off! [videorecording (Blu-Ray)] - Cameron, W. Bruce; Michon, Cathryn; Michon, Cathryn; McLendon-Covey, Wendi, 1969-; McLendon-Covey, Wendi, 1969-; McCarthy, Melissa, 1969-; Falcone, Ben, 1973-; Williams, Gary Anthony, 1966-; Nash, Niecy; Plotnick, Jack, 1968-; Bader, Diedrich, 1966-; Lamarr, Phil, 1967-; et al. (Lions Gate Entertainment, 2018)
Amateur 'chefs' from around the country compete for a million dollar prize in the ultimate food fight.